Synthesis, physical, chemical and biological properties of 7-ethylxanthinyl-8-aminoalkanoic acids’ derivatives - Dolhikh, O. P.; Romanenko, M. I.; Ivanchenko, D. H.; Aleksandrova, K. V.; Polishchuk, N. M.; Долгіх, Ольга Петрівна; Романенко, Микола Іванович; Іванченко, Дмитро Григорович; Александрова, Катерина Вячеславівна; Поліщук, Наталія Миколаївна; Долгих, О. П.; Романенко, Н. И.; et al. (Запорізький державний медичний університет, 2019)
Modern antibiotics and synthetic antimicrobial agents play a leading role in the treatment of bacterial infections. Despite their effectiveness, they cause a number of side effects, and thus the search for new antimicrobial and antifungal agents is currently one of the problems of pharmaceutical science of current interest. Literary data suggest that xanthine derivatives exhibit activity in relation to some strains of pathogenic microorganisms and fungi. The aim of this work is to develop a method for the synthesis of new derivatives of xanthine-8-aminoalkanoic acids and to study their physical and chemical properties, as well as their antimicrobial and antifungal effects. Materials and methods. The melting point has been determined with the help of an open capillary method with PTP-M device. Elemental analysis has been performed with the help of the instrument Elementar Vario L cube, NMR-spectra have been taken on a spectrometer Bruker SF-400 (operating frequency of 400 MHz, solvent DMSO, internal standard – TMS). Study of antimicrobial and antifungal activity of synthesized compounds has been performed by a two-fold serial dilution method. Standard test strains have been used for the study: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 885-653. Dimethylsulfoxide was used as the solvent of the compounds. Results. The reaction of 8-brom-7-ethylxanthines with an excess of the corresponding aminoalkanoic acid in an aqueous DMF medium in the presence of an equimolar (in relation to the amino acid) amount of baking soda leads to the formation of the corresponding 7-ethylxanthinyl-8-aminoalkanoic acids. Structure of synthesized compounds was definitely proved by 1Н NMR-spectroscopy. Conducting primary screening research of antimicrobial activity of 7-ethylxanthinyl-8-aminoalkanoic acids derivatives, which revealed moderate and weak activity in concentrations 50–100 mcg/ml. Conclusions. A preparative method of synthesis of not described in the literature 7-ethylxanthinyl-8-aminoalkanoic acids is developed. The structure of the synthesized compounds has been proved with the help of data of the 1H NMR spectroscopy. The antimicrobial and antifungal effects of the obtained compounds have been studied. The perspective of xanthine-8-alkanoic acids for the further search of biologically active compounds is shown. Сучасні антибіотики та синтетичні протимікробні засоби посідають чільне місце в лікуванні бактеріальних інфекцій. Незважаючи на їхню ефективність, вони викликають низку побічних ефектів, а отже пошук нових протимікробних і протигрибкових засобів нині є однією з найактуальніших проблем фармацевтичної науки. Дані фахової літератури свідчать, що похідні ксантину виявляють активність щодо деяких штамів патогенних мікроорганізмів і грибів. Мета роботи – розробка методу синтезу нових похідних ксантиніл-8-аміноалканових кислот і вивчення їхніх фізико-хімічних властивостей, протимікробної та протигрибкової дії. Матеріали та методи. Температуру плавлення визначали відкритим капілярним способом на приладі ПТП-М. Елементний аналіз виконали на приладі Elementar Vario L cube, ПМР-спектри зняті на спектрометрі Bruker SF-400 (робоча частота 400 МГц, розчинник ДМСО, внутрішній стандарт – ТМС). Вивчення антибактеріальної та протигрибкової активності синтезованих речовин здійснили за методом дворазових серійних розведень. Для дослідження застосували стандартні тест-штами: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 885-653. Як розчинник сполук використовували диметилсульфоксид. Результати. Реакція 8-бромо-7-етилксантинів із надлишком відповідної аміноалканової кислоти в середовищі водного ДМФА за наявності еквімолярної (щодо амінокислоти) кількості харчової соди призводить до утворення відповідних 7-етилксантиніл-8-амі-ноалканових кислот. Структура синтезованих сполук однозначно доведена методом 1H ЯМР-спектроскопії. Дослідження протимі¬кробної дії синтезованих сполук показали, що похідні 7-етилксантиніл-8-аміноалканових кислот виявляють помірну та слабку активність у концентраціях 50–100 мкг/мл. Висновки. Розроблена препаративна методика синтезу неописаних у фаховій літературі 7-етилксантиніл-8-аміноалканових кислот. За допомогою даних спектроскопії 1Н ЯМР доведена будова синтезованих сполук. Вивчена протимікробна та протигрибкова дія сполук, що отримали. Показана перспективність ксантиніл-8-алканових кислот для дальшого пошуку біологічно активних сполук. Современные антибиотики и синтетические противомикробные средства занимают лидирующее место в лечении бактериальных инфекций. Несмотря на их эффективность, они вызывают ряд побочных эффектов, следовательно, поиск новых противомикроб¬ных и противогрибковых средств – одна из самых актуальных проблем фармацевтической науки. Данные специализированной литературы свидетельствуют, что производные ксантина проявляют активность в отношении некоторых штаммов патогенных микроорганизмов и грибов. Цель работы – разработка метода синтеза новых производных ксантинил-8-аминоалкановых кислот и изучение их физико-хи¬мических свойств, противомикробного и противогрибкового действия. Материалы и методы. Температуру плавления определяли открытым капиллярным способом с использованием прибора ПТП-М. Элементный анализ выполнили на приборе Elementar Vario L cube, ПМР-спектры сняты на спектрометре Bruker SF-400 (рабочая частота 400 МГц, растворитель ДМСО, внутренний стандарт – ТМС). Изучение антибактериальной и противогрибковой активности синтезированных веществ проводили по методу двукратных серийных разведений. Для исследования использовались стандартные тест-штаммы: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 885-653. В качестве растворителя соединений использовали диметилсульфоксид. Результаты. Реакция 8-бром-7-этилксантинов с избытком соответствующей аминоалкановой кислоты в среде водного ДМФА в присутствии эквимолярного (по отношению к аминокислоте) количества пищевой соды ведет к образованию соответствую¬щих 7-этилксантинил-8-аминоалкановых кислот. Структура синтезированных соединений однозначно доказана методом 1Н ЯМР-спектроскопии. Исследование противомикробного действия синтезированных соединений показало, что тиопроизводные 7-этилксантинил-8-аминоалкановых кислот проявляют умеренную и слабую активность в концентрациях 50–100 мкг/мл. Выводы. Разработана препаративная методика синтеза неописанных в спецаилизированной литературе 7-этилксантинил-8- аминоалкановых кислот. С помощью данных спектроскопии 1Н ЯМР доказано строение синтезированных соединений. Изучено противомикробное и противогрибковое действие полученных соединений. Показана перспективность ксантинил-8-алкановых кислот для дальнейшего поиска биологически активных соединений.
Синтез, фізико-хімічні та біологічні властивості похідних 7-етилксантиніл-8-аміноалканових кислот
Синтез, физико-химические и биологические свойства производных 7-этилксантинил-8-аминоалкановых кислот
Keywords: ксантин; органічний синтез; ПМР-спектроскопія; антибактеріальні, протигрибкові засоби; органический синтез; ПМР-спектроскопия; антибактериальные, противогрибковые средства